2016
DOI: 10.5812/archcid.36648
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Genotype Analysis of Blastocystis hominis in Iran: A Systematic Review and Meta-Analysis

Abstract: Context: Blastocystis hominis is a unicellular protozoan found commonly in the intestinal tract of humans and many other animals with multiple subtypes, which tend to be specific to the host. We aimed to apply a meta-analysis for studies of protozoan pathogens in order to obtain a general overview of the prevalence and genotype analysis of Blastocystis spp. in Iran.Evidence Acquisition: International electronic databases such as PubMed, Scopus, ISI Web of Science, Ovid, Google scholar, and national databases i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 55 publications
(28 reference statements)
0
18
0
Order By: Relevance
“…in Iran was 3% between 2003 and 2015, and the results showed that prevalence of Blastocystosis had a decreasing trend in Iran. 8 The survived population, sample size, diagnostic method and personal and community hygiene could affect the prevalence of Blastocystis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…in Iran was 3% between 2003 and 2015, and the results showed that prevalence of Blastocystosis had a decreasing trend in Iran. 8 The survived population, sample size, diagnostic method and personal and community hygiene could affect the prevalence of Blastocystis.…”
Section: Discussionmentioning
confidence: 99%
“…7 The prevalence rate of Blastocystis is 1.5%-20% in industrialized countries, while it is 30%-50% in developing countries. 8 Epidemiological studies have indicated that the prevalence of Blastocystis in human has been estimated from 0.5 to 54.4% in different parts of Iran. [8][9][10][11][12][13][14] Based on the sequence analysis of the small subunit ribosomal ribonucleic acid (SSU-rRNA) gene, at least 17 subtypes (STs) of Blastocystis have been identified in humans and animals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of Blastocystis spp in developed countries is 1.5% -10% and 30% -50% in developing countries (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…This parasite exists in the large intestine of human and other vertebrates. It is probably the most common intestinal protozoa in humans around the world and particularly in Iran (3,4). Its prevalence in developed countries is between 1.5 -20% and in developing countries it can reach to 30 -50% (5,6).…”
Section: Introductionmentioning
confidence: 99%